Bank filtration for climate resilience: potentiality of a new site along the Ismailia Canal in Egypt - Ghodeif, Kamal; Wahaab, Rifaat A.; Grischek, Thomas; Afifi, Hana; Wahsh, Neveen (Geologos, 2022)
Bank filtration (BF) is a nature-based solution that can provide safe drinking water at a low cost, in being a green tech- nology that benefits from natural ecosystem services and saves energy as well. The objective of the present paper is to evaluate the potentiality of a new site for bank filtration along a surface water source that experiences periods of both high and low flow. This site is located along the Ismailia Canal in the eastern Nile Delta fringe of Egypt. The present evaluation is based on exploratory drilling, installation of monitoring infrastructure and monitoring of both water level and water quality parameters for one year. The site has favourable hydrogeological conditions; the mean hydraulic conductivity of aquifer materials (sand and gravel) is 18.98 m/day. Moreover, there is a hydraulic connection between canal and aquifer; under steady conditions, the canal feeds the aquifer. Using different tracers, such as Cl, EC, Sr and SO4, the average bank filtration share is in excess of 95%. BF has reduced the particulates (turbidity) by 96%, total col- iform by 99 % and total organic carbon (TOC) expressed as ultra-violet absorbance at 254 wavelengths (UVA254) by 44%. In addition, BF reduces concentrations of disinfection by-products due to its ability to remove organic matter. The potential degradation of TOC in the canal bed sediments may cause the release of iron (Fe) and manganese (Mn) to the bank filtrate water; this process is exaggerated during low-flow periods. Compared to conventional water treatment, BF is a cost-effective green technology, because no chemicals are used and no waste products are generated.